HIV Testing and PrEP Use in a National Probability Sample of Sexually Active Transgender People in the United States - Sevelius, Jae M. (J Acquir Immune Defic Syndr, 2020)
HIV testing and pre-exposure prophylaxis (PrEP) are effective HIV prevention strategies often underused by transgender people. METHODS: Recruitment occurred in 2 phases to identify transgender respondents in a probability sample of adults in the United States. Transgender respondents completed a self-administered paper or web-based survey designed to assess transgender population health. Sexually active respondents (HIV-negative and had sex in the 5 years previously, N = 190) and a subsample of those at risk for sexual HIV acquisition (sex with cisgender men or transgender women, n = 120) were included in analyses. RESULTS: Of the full sample of sexually active respondents, those who were transfeminine were less likely to be familiar with PrEP; most (72%) reported favorable attitudes toward PrEP. Of those at risk for HIV acquisition, 23% had never tested for HIV. Respondents of color were more likely than white respondents to meet Centers for Disease Control and Prevention recommendations for HIV testing. Respondents who met Centers for Disease Control and Prevention recommendations for HIV testing were more likely to report looking online for lesbian, gay, bisexual, and transgender or transgender-specific health information. Few respondents reported currently taking PrEP (3%); those who reported higher levels of nonaffirmation of their gender identity were less likely to currently use PrEP. DISCUSSION: These findings may indicate some success of HIV testing outreach programs that prioritize people at higher risk for acquiring HIV, focusing on those who are vulnerable to structural marginalization. Ongoing public health efforts are needed to increase HIV testing and PrEP awareness among transgender adults, who are disproportionately impacted by HIV.